A Study on the Value System of Nujiang Lisu Costume in Yunnan, China - Zhu, Yang Yang; Faridah, Sahari (Aliva Global Research and Development, 2021)
As an essential part of China's intangible cultural heritage, the Lisu costume in Nujiang, Yunnan, has accumulated rich value after long-term development. In recent years, China has attached great importance to protecting intangible cultural heritage, and the government has increased its efforts to excavate and protect national culture. Under the background of the upsurge of traditional cultural protection, the preservation of Lisu costumes located in remote areas of China is gradually receiving attention. The value of Lisu costumes should be explored in depth to provide the internal driving force for the sustainable development of the ethnic costume. This article uses the methods of fieldwork survey, questionnaire survey, and inductive analysis to conduct a comprehensive research. The researcher personally felt and verified the value of Lisu costumes through the method of fieldwork, collected statistics on the attitude of Lisu people about the costume value through the method of the questionnaire survey, matched the multiple values of Lisu costume into Stolovich's artistic value system theory through the method of inductive analysis. The researcher concluded that the Lisu costume has fifteen types of costume values, and eventually constructed a complete framework of the Lisu costume value system. The results of this research provide reasonable ideas for the evaluation of the Lisu costume value in contemporary society. They are suitable for self-evaluation of Lisu costumes in Nujiang, to understand the significance and value of the costume in modern society, as well as to form a scientific and effective basis for the conservation and development of Lisu costume. Keywords: Value system, Costume, Stolovich, Lisu ethnic, Nujiang Prefecture.